2016
DOI: 10.1080/09168451.2016.1200455
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-137 affects melanin synthesis in mouse melanocyte by repressing the expression ofc-KitandTyrp2inSCF/c-Kitsignaling pathway

Abstract: Previously, we created miR-137 overexpressing transgenic mice that produced lighten color phenotypes including gray mice phenotype. However, the miR-137 functional role in coat color regulation is still not well understood. In this study, the quantity of melanin granule and the relative expression of TYRP2 in gray miR-137 overexpression transgenic mouse skin were significantly lower than that in C57BL/6J black mouse skin. The mRNA and protein expression level of c-Kit and c-Kit downstream gene Tyrp2 in miR-137… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Similarly, in mouse skin melanocytes, we found that miR-21a-5p targets SOX5 through the MITF pathway, and miR-27a-3p regulates Wnt3a to modulate melanogenesis [23,24]. Transgenic mice overexpressing miR-137 can change coat color, and miR-137 could inhibit the pigmentation of mouse skin melanocytes by the SCF/c-Kit pathway [25]. In contrast, miR-488 could degrade POMC mRNA in keratinocytes to modulate mice coat color by the α-MSH/ MC1R pathway [26].…”
Section: Introductionmentioning
confidence: 68%
“…Similarly, in mouse skin melanocytes, we found that miR-21a-5p targets SOX5 through the MITF pathway, and miR-27a-3p regulates Wnt3a to modulate melanogenesis [23,24]. Transgenic mice overexpressing miR-137 can change coat color, and miR-137 could inhibit the pigmentation of mouse skin melanocytes by the SCF/c-Kit pathway [25]. In contrast, miR-488 could degrade POMC mRNA in keratinocytes to modulate mice coat color by the α-MSH/ MC1R pathway [26].…”
Section: Introductionmentioning
confidence: 68%
“…Indeed, miR‐137 was initially shown as a regulator of MITF in human melanoma cell lines . In a second study, the overexpression of miR‐137 was followed by the downregulation of KIT and TYRP2 genes and reduction of melanin content in mouse skin melanocytes . In this latter study, KIT was evidenced as a direct target of miR‐137.…”
Section: Non‐coding Rnas and The Regulation Of Melanogenesismentioning
confidence: 90%
“…Of note, most of the miR-encoding DEGs (11 out of 13) had the other DEGs as their predicted targets (Table III), the majority of which were significantly decreased in grey compared with black hair follicles. Furthermore, among the miR-targeted DEGs, two genes (syndecan binding protein and KIT) are involved in pigment-associated pathways (26,27).…”
Section: Resultsmentioning
confidence: 99%